Protective Effects of Lycopene and Tomato Extract Against Doxorubicin-Induced Cardiotoxicity: Cardioprotective effect of lycopene - Karimi, Gholamreza; Ramezani, Mohammad; Abdi, Azadeh (Iranian Journal of Pharmaceutical Sciences, 2005)
The protective effect of tomato extract and lycopene on acute doxorubicin-induced myocardial toxicity was evaluated in mice. Doxorubicin toxicity, induced by a single intraperitoneal injection (15 mg/kg), was revealed by elevated serum CPKMB and histopathological observations. Tomato extract (1.2 and 2.4 g/kg, i.p.) and lycopene (1.7 and 3.5 mg/kg, i.p.), prevented the rise in serum CPKMB and ameliorated cardiac cell injury. These results suggest that tomato extract and lycopene inhibit doxorubicin-induced cardiotoxicity and might serve as a combination chemotherapeutic agent with doxorubicin to limit its cardiotoxic effects.